DESAIN SALURAN TERBUKA BERBASIS MICROSOFT EXCEL: Perhitungan dan Pemodelan yang Praktis dan Effisien - Faizal Agung Riyadi; Nurkhamim; Supandi; Cahyadi, Tedy Agung (Institut Teknologi Nasional Yogyakarta, 2019)
A channel is constructed as a media for water to flow. Phases of plan, design, and construction of a channel require a lot of time, effort, and budget. Design and construction of a channel need to be suited to certain requirements and characteristics of the location. Changes of design parameters often occurred as a result of technical and economical considerations. It leads to changes of channel design to adapt to the new parameters. Hence, the needs of tool to ease the calculation of channel design. Required parameters for channel design calculations are flow (Q), Chezyâ€™s resistance factor (C), Darcy-Weisbachâ€™s coefficient (f), atau Manningâ€™s roughness factor (n), and the channel base gradient (i). The objective of this research are channel design calculations and modelling, in addition profide a tool which is practical and easy to use. The methods are Chezy, Darchy-Weisbach, and Manning formula to calculate the design of varied channel type using Microsoft Excel software. Determinations of Chezyâ€™s resistance factor (C), Darcy-Weisbachâ€™s coefficient (f), can be related to Manningâ€™s roughness factor (n) value. Manningâ€™s roughness factor (n) can be estimated from the size of channel bedâ€™s lining material particles (d) using certain formula or define the value dirrectly from Manningâ€™s roughness factor table.The result of this research including a tool for open channel design calculation and modellingâ€œKalkulator Desain Saluran â€“ FARâ€. The writers propose a new formula to estimate Manningâ€™s roughness factor (n) value from the size of channel bedâ€™s lining material particles (d). In addition, the writers propose formulas to directly calculate water level on the channel geometry section (y). The formula include coefficient of Î± which is based on relations of channel geometry parameters in to the formula of Chezy, Darchy-Weisbach, and Manning.